The Toxic Masculinity in Anthers and Stars by Kraei (2019): Toxic masculinity in Anthers and Star by Kraei (2019) - Alfini, Restu (English Language, Linguistics, Literature, And Education Journal, 2022)
This research aims to show what kinds of figurative language are found in the poems anthology Anthers and Stars by Kraei. And describe the masculinity found from the explanation of figurative language. This research is a qualitative descriptive study. The writer uses theory of masculinity by Connell and Messerschimdt (2005). The subject of this research 2 chapters Anthers and Stars  is the poetry anthology The Great Fairy Ritual by Kraei 2019. Data analysis uses qualitative descriptive techniques that produce descriptive data presentations in the form of sentences or words contained in the anthers and stars. the way of data collection is done by reading technique and note-taking technique. The results of this study indicate the use of figurative language, namely: metaphor, hyperbole, synecdoche, paradox, symbol, simile. figurative language found to be associated with toxic masculinity. In his poems, the characters are being described by their assigned sex and how the society perceived them with stigmas that highly attached with themselves. By using figurative language, writer found to describe and address this issue of masculinity in the poem.